Biodiversity Hotspots and Conservation Priorities in Tropical Asia - Takahashi, Haruto; Fujita, Miku; Nishida, Daiki (Journal of Selvicoltura Asean, 2024)
Tropical Asia is home to a rich diversity of species and ecosystems, yet it faces significant threats from habitat loss, climate change, and human activities. Identifying biodiversity hotspots in this region is crucial for prioritizing conservation efforts and ensuring the protection of unique species and habitats. This research aims to evaluate biodiversity hotspots in tropical Asia and establish conservation priorities based on ecological significance and vulnerability. The study seeks to provide actionable recommendations for policymakers and conservationists to enhance biodiversity preservation in these critical areas. A spatial analysis was conducted using geographic information systems (GIS) to map biodiversity hotspots across tropical Asia. Data from various sources, including species distribution records and habitat assessments, were analyzed to identify regions with high biodiversity and significant conservation needs. Stakeholder interviews were also conducted to gather insights on local conservation challenges. The findings revealed several key biodiversity hotspots, including the Indo-Burma region and the Sundaland region, which are critically endangered due to deforestation and habitat fragmentation. The analysis indicated that targeted conservation efforts in these areas could significantly enhance species protection and ecosystem resilience. This study concludes that prioritizing conservation actions in identified biodiversity hotspots is essential for mitigating biodiversity loss in tropical Asia. Collaborative efforts among governments, NGOs, and local communities are vital to developing effective conservation strategies that address both ecological and socio-economic challenges.